A Case of a Spontaneous Intraorbital Arteriovenous Fistula: Clinico-Radiological Findings and Treatment by Transvenous Embolisation via the Superior Ophthalmic Vein*. (April 2013) - Naqvi, Jawad; Laitt, Roger; Leatherbarrow, Brian; Herwadkar, Amit
Abstract A 72-year-old male presented with progressive right axial proptosis and red eye. Catheter angiography demonstrated an intraorbital arteriovenous fistula (IAVF) distal to the central retinal artery (CRA). Transvenous embolisation following direct surgical exposure of the superior ophthalmic vein (SOV) resulted in rapid resolution of his symptoms and signs. Transvenous embolisation via the SOV is a safe, effective alternative to transarterial embolisation for treating spontaneous IAVF where transarterial embolisation poses a risk of CRA occlusion.